Anthropometric and metabolic determinants of 6,000-m rowing ergometer performance in internationally competitive rowers - Mikulic, P. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to examine the anthropometric and metabolic determinants of performance during 6,000-m of rowing on an ergometer. The sample comprised 25 internationally successful male heavyweight rowers (mean ± SD: age 22.2 ± 4.8 years, rowing experience 8.8 ± 4.6 years, stature 1.91 ± 0.05 m, body mass 91.7 ± 5.9 kg, maximal oxygen uptake 5.53 ± 0.30 L·min-1). The rowers completed an incremental maximal exercise test on a rowing ergometer and, within 2 weeks of this test, also completed a 6,000-m rowing ergometer time trial (mean ± SD: 1195.4 ± 36.1 seconds). The strongest correlates (r > 0.5, p < 0.05) with performance were lean body mass (r = -0.767), power output at ventilatory threshold (r = -0.743), power output at maximal oxygen uptake (r = -0.732), body mass (r = -0.693), chest girth (r = -0.598), relaxed arm girth (r = -0.574), forced vital capacity (r = -0.519), and arm span (r = -0.505). Stepwise multiple linear regression procedures indicated that the model comprising a combination of anthropometric and metabolic variables is the best predictor of performance (adjusted R2 = 0.722), followed by models comprising anthropometric (adjusted R2 = 0.575) and metabolic (adjusted R2 = 0.530) variables alone. The results suggest that 6,000-m ergometer performance is determined mainly by power output at ventilatory threshold (58.7% of explained variance). Based on the obtained correlations and regression models, it can be concluded that rowers competing over a 6,000 m distance on a rowing ergometer should devote their training time to the improvement of lean body mass and to the improvement of power output corresponding to ventilatory threshold.